2019
DOI: 10.1177/1524839919845669
|View full text |Cite
|
Sign up to set email alerts
|

Heart Attack and Stroke Symptoms Knowledge of Native Hawaiians and Pacific Islanders in the United States: Findings From the National Health Interview Survey

Abstract: Native Hawaiians and other Pacific Islanders (NHPI) suffer disproportionate rates of death from heart attack and stroke; however, little is known about NHPI heart attack and stroke symptoms knowledge. We used multivariable logistic regression to examine associations between heart attack and stroke symptoms knowledge and electronic health (eHealth) use, education, engaging in health risk behaviors, and having an at-risk diagnosis or a past heart attack and/or stroke. The analytic sample included 2,172 NHPI adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…African-American men who had lower levels of education and low income showed low CVD knowledge score [16]. Hawaiians in the United States reported moderate to high levels of heart attack and stroke symptom knowledge [17]. Cardiovascular risk factors and knowledge of symptoms among Vietnamese Americans showed that only 59% of Vietnamese Americans knew that chest pain was a symptom of heart attack [18].…”
Section: Discussionmentioning
confidence: 99%
“…African-American men who had lower levels of education and low income showed low CVD knowledge score [16]. Hawaiians in the United States reported moderate to high levels of heart attack and stroke symptom knowledge [17]. Cardiovascular risk factors and knowledge of symptoms among Vietnamese Americans showed that only 59% of Vietnamese Americans knew that chest pain was a symptom of heart attack [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, individuals who smoke or drink showed lower awareness of stroke and MI symptoms, which was consistent with previously reported results ( 13 , 16 , 20 , 21 ). Hypertension, diabetes, and dyslipidemia also increase the risk of stroke and MI ( 1 , 4 ), and past studies have revealed that patients with the above underlying diseases had stronger awareness of CVD symptoms ( 13 , 21 , 27 ). This may be because these patients regularly visited doctors and learned about the complications, including stroke and MI ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of undiagnosed high blood pressure paired with reduced frequency of health care provider visits for those with undiagnosed high blood pressure poses a significant concern, because hypertension is a leading risk factor for heart attack and stroke [1,37], and prior literature has demonstrated that NHPI have an increased rate of stroke morbidity and mortality [14,38,39]. Furthermore, prior literature among NHPI has documented limited knowledge related to heart attack and stroke [40]. The high risk related to undiagnosed high blood pressure combined with a lack of heart attack and stroke knowledge demonstrates a need for accessible hypertension screening and culturally appropriate health education among Marshallese.…”
Section: Plos Onementioning
confidence: 99%